The impact of playing area dimension and team imbalance on the performance of individual tactical actions in soccer ball possession - Nunes, N. A.; Corsie, M.; Dye, S.; Maidment, M.; Travassos, B. (International Journal of Performance Analysis in Sport, 2025)
This study analyses the effects of spatial constraints and team imbalances on individual actions during possession-based soccer small-sided games (SGGs), when varying levels of opposition and cooperation. Eighteen university-level semi-professional players participated in SSGs on artificial turf across small, medium, and large playing areas. Individual actions, including dribbling, passing, tackling, blocking, and intercepting, were recorded and analysed using the Kruskal-Wallis and Dwass-Steel-Critchlow-Fligner tests. Data were analysed from an opposition perspective by positioning four players against 3-5 opponents (4v3 to 4v5) to evaluate superiority versus inferiority, and from a cooperation perspective, when incorporating additional teammates into a team of 2, ranging from 1 to 3 (4v2 + 1 to 4v2 + 3). In opposition-based scenarios, smaller areas facilitated more actions such as dribbling, blocking and intercepting, while medium areas in numerically inferior conditions promoted passing. From a cooperation-based perspective, smaller and medium-sized areas increased defensive actions like tackling and intercepting, while larger areas encouraged dribbling. In high cooperation scenarios, smaller areas required more frequent individual actions across all variables. Coaches can use smaller playing areas to increase individual actions like passing and intercepting. Larger areas promoted individual creativity, such as dribbling and spatial awareness, while encouraging coordinated team play in high cooperation scenarios.